2005
DOI: 10.1038/ng1604
|View full text |Cite
|
Sign up to set email alerts
|

Variants of ENPP1 are associated with childhood and adult obesity and increase the risk of glucose intolerance and type 2 diabetes

Abstract: We identified a childhood obesity locus on chromosome 6q16.3-q24.2 1 that includes 2.4 Mb common to eight genome scans for Type 2 diabetes (T2D) or obesity 1-8 . Analysis of the ENPP1 (PC-1) gene, a candidate for insulin resistance 9,10 in 6,147 subjects revealed association between a three allele risk haplotype (K121Q/IVS20 delT-11/A>G +1044 TGA, QdelTG) and childhood obesity (OR=1.69, p=0.0006), and in adults with morbid or moderate obesity (OR= 1.50, p= 0.006, OR= 1.37, p= 0.02) and also with T2D (OR=1.56, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
248
8
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(281 citation statements)
references
References 24 publications
17
248
8
8
Order By: Relevance
“…Therefore, klotho belongs to the group of key factors regulating mineral and vitamin D metabolism. (c) ENPP1, known to be the gene for insulin resistance/type 2 diabetes, hyperglycemia, and obesity (Meyre et al 2005), was recently shown by us and others to be associated with osteoporosisrelated traits (Cheung et al 2010). (d) Activation of the nuclear protein deacetylase Sirt1 (an antioxidant protein involved in aging) has recently been shown to decrease adipocyte development from preadipocytes, therefore promoting differentiation of mesenchymal stem cells into osteoblasts via inhibition of PPARγ (Backesjo et al 2009).…”
Section: Pleiotropymentioning
confidence: 99%
“…Therefore, klotho belongs to the group of key factors regulating mineral and vitamin D metabolism. (c) ENPP1, known to be the gene for insulin resistance/type 2 diabetes, hyperglycemia, and obesity (Meyre et al 2005), was recently shown by us and others to be associated with osteoporosisrelated traits (Cheung et al 2010). (d) Activation of the nuclear protein deacetylase Sirt1 (an antioxidant protein involved in aging) has recently been shown to decrease adipocyte development from preadipocytes, therefore promoting differentiation of mesenchymal stem cells into osteoblasts via inhibition of PPARγ (Backesjo et al 2009).…”
Section: Pleiotropymentioning
confidence: 99%
“…One ENPP1 haplotype is associated with childhood and morbid obesity, T2DM, as well as circulating levels of ENPP1. [144][145][146] Expression of a long ENPP1 mRNA isoform, which includes one of the SNPs defining the risk haplotype, is specific for pancreatic islet beta cells, adipocytes and liver. 144 In addition, one ENPP1 SNP may impair insulin binding to the insulin receptor.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…[144][145][146] Expression of a long ENPP1 mRNA isoform, which includes one of the SNPs defining the risk haplotype, is specific for pancreatic islet beta cells, adipocytes and liver. 144 In addition, one ENPP1 SNP may impair insulin binding to the insulin receptor. 144 Two recent reports including several thousand subjects of European ancestry have not confirmed association between the ENPP1 haplotype and obesity or T2DM.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…OR values recently found for a candidate protein associated with insulin resistance are of 1.56 for type II diabetes and ranged between 1.37 and 1.69 for childhood or adult obesity. 30 To understand how the PPP2R2C gene might be implicated in the pathology, we searched for interacting proteins by performing a Y2H screening of a human brain cDNA library with the PP2A-Bg subunit as a bait. Among positive clones, we focused our attention on two new splice variants of brain-specific KCNQ2 channels, 18,31 Q2-3H2 and Q2-3H9.…”
Section: Pp2a-bc and Kcnq2 In Bipolar Diseasementioning
confidence: 99%